Construção e aplicação analítica de espectrômetro de emissão atômica com atomização eletrotérmica em filamento de tungstênio - Gonzalez, Mário Henrique (2011)
This thesis has two lines of development based on measurements of atomic emission using a tungsten coil electrothermal atomizer. The first line dealt with the construction of a tungsten coil atomic emission spectrometer (WCAES) with a portable monochromator connected to an array of charge-coupled devices as the detection system. Afterwards, the measurement of atomic emission by clouds generated by electrothermal atomization/excitation in a tungsten coil was evaluated. Instrumental conditions for measurements of transient emission signals, such as the position of the coil related to the entrance slit of the monochromator, the transfer of emitted radiation by the decay of excited atoms, and the sensitivity of array detectors, were critically evaluated. After establishing the instrumental conditions, the measurements of transient emission signals for Co and Mn were studied and applied for the determination of these metals. In this step, the occurrence of interferences due to the non-isothermal character of the open atomizer was systematically evaluated. The limits of detection (LOD) were approximately 0.33 to 0.48 mg/L for different cobalt emission lines and relative standard deviations (RSD) typically varied from 4.3 to 6.5 %. Spectral interferences were observed in the presence of Ni. For Mn, the performance parameters were LOD 0.54 to 0.65 mg/L and RSD 5.9 to 6.5 %. Using a strategy based on the summation of signals, LOD was 0.17 mg/L and RSD 1.7 %. Spectral interferences were observed in the presence of Al, Ca and Na. The developed methods were applied for accurate determination of Co and Mn in medicines and industrial alloy samples. Accuracy was determined with two certified reference materials: San Joaquim soil (NIST 2709) and industrial sludge (NIST 2782). Results obtained by WCAES were in agreement with ICP OES at a 95 % confidence level. The WCAES is simple and low cost equipment for performing analysis based on emission measurements, but requires the development of tailored analytical procedures for controlling matrix interferences.